Петр Леонидович Капица – основоположник техники сильных импульсных магнитных полей - Баранов, Михаил Иванович (НТУ "ХПИ", 2005)
Приведен краткий исторический очерк по проблеме получения сильных постоянных и импульсных магнитных полей. Отмечен значительный вклад выдающегося советского физика-экспериментатора Капицы П. Л. в решение данной проблемы.

A brief sketch on the history of the problem of strong constant and pulsed magnetic field generation is given. A significant contribution of the prominent Soviet physicist-experimentalist P. L. Kapitza to solution of this problem is described.
Peter Leonidovich Kapitza - founder of strong pulsed magnetic field engineering.
Keywords: магнитное поле; электротехника; импульснве токи; Капица Петр Леонидович; history; generation; problem; strong constant fields; electrophysical installations; pulsed magnetic fields